Mindset dan task value: Dapatkah memprediksi kinerja siswa Sekolah Dasar (SD) pada bidang matematika? - Pratiwi, Bellita Nusa; Royanto, Lucia R.M. (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2020)
AbstractThe mathematical ability of Indonesian students is still lacking, especially when working on problems that require reasoning. Task value (which consists of intrinsic and attainment/utility values) and growth mindset were considered as factors that can influence student performance in performing complex tasks such as mathematics. A hypothesis formulated based on the purpose of this study as there is an effect of intrinsic value, attainment/utility value, and mindset on elementary student performance in mathematics. The variables in this study were measured by: 1) Subjective Task Value scale (? intrinsic value = 0.87; ? attainment / utility value = 0.79); 2) Implicit Theories of Intelligence scale for mindset (? = 0.84), and 3) mathematical tests (? = 0.84). The subjects of this study were 371 5th grade students in five schools in Jakarta selected by convenience sampling technique. Data processed with Multiple Regression techniques using IBM SPSS 22 for Windows. The analysis showed that the mindset had a greater role than the intrinsic value in predicting mathematical abilities. Also, the attainment/utility value did not significantly predict the performance of 5th-grade students.Keywords: Elementary School Students; Mathematics; Mindset; Task Value. AbstrakTingkat kemampuan matematika para siswa Indonesia pada umumnya masih tergolong kurang, terutama saat mengerjakan soal yang membutuhkan penalaran. Task value (yang terdiri dari intrinsic dan attainment/utility value) dan growth mindset dipertimbangkan sebagai faktor-faktor yang dapat memengaruhi kinerja siswa dalam mengerjakan tugas rumit seperti matematika. Tujuan penelitian ini dituangkan dalam suatu hipotesis yaitu terdapat pengaruh skor intrinsic value, attainment/utility value, dan mindset terhadap kinerja siswa SD dalam matematika. Variabel-variabel dalam penelitian ini diukur dengan: 1) skala Subjective Task Value (? intrinsic value = 0,87; ? attainment/utility value = 0,79); 2) skala Implicit Theories of Intelligence untuk mindset (?=0,84), dan 3) tes matematika (?=0,72). Subjek penelitian ini adalah 371 siswa kelas 5 SD pada lima sekolah di Jakarta yang dipilih dengan teknik convenience sampling. Data diolah dengan teknik Multiple Regression menggunakan IBM SPSS 22 for Windows. Hasil analisis menunjukkan bahwa mindset memiliki peranan yang lebih besar daripada intrinsic value dalam memprediksi kemampuan matematika. Selain itu, attainment/utility value tidak secara signifikan memprediksi kinerja siswa kelas 5 SD. Kata kunci: Matematika; Mindset; Siswa SD; Task Value.